Pattern of illnesses presenting as acute abdomen: surgical study in 118 patients - Kumar, Rajesh; Ray, Mriganko S. (International Surgery Journal, 2021)
Background: Acute abdomen is an important clinical entity and represents a symptom complex; of which, pain in the abdomen is a predominant feature. It is the result of some underlying condition and is a very common reason for patients reporting to emergency department. Pattern of illnesses presenting as ‘acute abdomen’ can vary from mild to life threatening in severity and management can similarly vary from just symptomatic relief to emergency operative intervention. It poses a significant challenge for the clinician since he is required to untangle the issue in a limited time frame and formulate a management plan. The aim of the study was finding the pattern of underlying conditions which had resulted in patients presenting with acute abdominal pain. Methods: A prospective observational study was carried out on 118 patients who reported with ‘acute abdomen’, from August 2015 to February 2017. Results: In this study, pattern of illnesses reflected that benign biliary disease was the commonest condition in the study population. This was followed by urolithiasis. An important observation was that ‘non-specific abdominal pain’ (NSAP) was the reason for acute abdomen in about 14% patients. Many other conditions like acute appendicitis, hollow viscus perforation, intestinal obstruction and pancreatitis presented with similar symptom complex in which abdominal pain was the main feature. Conclusions: At the end of the study, we had a better knowledge of the conditions presenting as acute abdomen in the source population and the same can be utilized for further research in the field of this important clinical entity.